Systemtic Review of The Studies Investigating Parents' Social Media Posts About Their Children in Türkiye - Serap Kal Korkmaz; Yiğit Emrah Turgut (Yeni Medya)
This research aimed to reveal the general trends of the studies on parents' social media posts about their children in Türkiye. For this purpose, 36 studies that met the research criteria were included out of 79 in the National Thesis Centre, Dergipark, TR Index, Web of Science, Scopus, and ERIC databases. The research’s findings revealed that studies on sharenting behavior in Türkiye have primarily been published in the National Thesis Center database, with a notable increase in publications in 2022. In these studies, a qualitative research approach has mostly been adopted, surveys have been used for data collection, and the data have been analyzed using content analysis techniques. In addition, special moments such as first step/first tooth, birthday celebration, new year celebration, and graduation ceremony/year-end performance were prominent in parents' social media posts about their children. Parents shared these posts for socialization, feeling happy, exchanging ideas about their parenting, collecting memories, commercial gain, and seeking parental approval. While these sharing had emotional effects on the parent, including feeling happy and having a fun time, as well as educational effects, including acquiring information, they had the highest violation and the lowest emotional effect on the child.